2014
DOI: 10.1007/s00343-015-4013-1
|View full text |Cite
|
Sign up to set email alerts
|

Tests of new in-situ seabed acoustic measurement system in Qingdao

Abstract: A new in-situ seabed acoustic measurement system is developed for direct in-situ measurement of sediment geoacoustic properties (compressional wave velocity and attenuation). The new in-situ system consists of two parts: the deck control unit and the underwater measurement unit. The underwater measurement unit emits sonic waves that propagate through the seafl oor sediment, receives the returning signals, and transmits them to the deck control unit for waveform display and analysis. The entire operation is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Wang et al [34] had researched the relation between the acoustic characters of sea bottom sediment and seawater depth, they found that when the water depth less than 1000 m, the influence of depth on sound velocity can be ignored. In fact, changes in temperature and pressure are inevitable for sampling measurement, thus, the development of in situ measurement techniques is important for the measurement of sound velocity in seafloor [35].…”
Section: Sound Velocitymentioning
confidence: 99%
“…Wang et al [34] had researched the relation between the acoustic characters of sea bottom sediment and seawater depth, they found that when the water depth less than 1000 m, the influence of depth on sound velocity can be ignored. In fact, changes in temperature and pressure are inevitable for sampling measurement, thus, the development of in situ measurement techniques is important for the measurement of sound velocity in seafloor [35].…”
Section: Sound Velocitymentioning
confidence: 99%
“…1. In situ measurements: Since the 1990s, several in situ techniques have been developed and used to measure acoustic properties, including the in situ sediment geoacoustic measurement system (Richardson and Briggs, 1996), sediment acoustic and physical property apparatus (Best et al, 2001), in situ sound speed and attenuation probe (ISSAP) (Kraft et al, 2002), acoustic lance (AL) (Fu et al, 2004), sediment acoustic speed measurement system (Yang et al, 2008), multifrequency in situ geoacoustic measurement system (Tao et al, 2009), hydraulicdriven in situ sediment acoustic measurement system (HSISAMS) (Kan et al, 2011), drag-type in-situ acoustic measurement system (Hou et al, 2014), the ballast in situ sediment acoustic measurement system (BISAMS) (Wang et al, 2018). These can obtain the closest approximation to the real data, but at the highest cost and with complex operational processes; currently, such measurements have only been applicable to the shallow seafloor.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the sampling measurement, in situ measurement introduces less disturbance to the seafloor sediment (especially deep‐sea soft sediments), and the environmental temperature and pressure will not change during the measurement, resulting in more accurate results that reflect the actual state of the seafloor sediments. Various techniques have been developed for acoustic in situ measurement of seafloor sediment, mainly including the in situ sediment acoustic measurement system (Richardson & Briggs, 1996), the acoustic lance (Gorgas et al., 2002), the hydraulic‐driven in situ sediment acoustic measurement system (Liu et al., 2013), the acoustic coring system assembled with a gravity core (Megan et al., 2019), the drag‐type in situ acoustic measurement system (Hou et al., 2014), the sediment acoustic‐speed measurement system (SAMS) (Yang & Jackson, 2020) and the ballast in situ acoustic measurement system (Li et al., 2019; Wang et al., 2018). These techniques have been widely applied in studying the acoustic properties of seafloor sediment in different marine regions.…”
Section: Introductionmentioning
confidence: 99%